The Impact Of Bank-specific And Macroeconomic Factors On Banks Profitability: Panel Evidence From Algeria - Bensalem, Farah; Gaidi, Khemissi (جامعة الوادي - University of Eloued, 2021)
This paper investigates the impact of bank-specific and macroeconomic variables on banks’ profitability in Algeria during (2012-2019). For this purpose, Return on assets and return on equity are taken as indicators of the banks’ profitability. On the other hand, the factors affecting the profitability of banks were divided into two categories: bank-specific variables, and macroeconomic variables. To this end, a random effect model of Panel Data used to analyze the data. Therefore, the study results revealed that capital adequacy, efficiency, and inflation are among the independent factors that have a statistically significant effect on commercial banks’ profitability operating in Algeria.
مقال
Keywords: Profitability ; bank-specific ; macroeconomic ; Panel data ; Algeria